Internal Jugular Microembolic Signal Detection in a Patient with Cerebral Sinus Thrombosis Complicated by Pulmonary Embolism. Issue 2 (June 2017) - Sekhar, Laligam; Becker, Kyra; Moore, Anne; Tran, Vanessa
A 40-year-old woman with prior history of headaches, left-sided weakness, and diplopia was diagnosed with right sigmoid and transverse sinus thrombosis; increased intracranial pressure and associated cerebral venous infarction that underwent 12 months anticoagulation and then stopped. She has been off anticoagulation for about a year then started not "feeling right, " and was diagnosed with pneumonia and pulmonary embolism. During her course of hospitalization, she presented with progressive headache, possible left-sided weakness, associated blurry vision, nausea, and vomiting. Magnetic resonance venogram (MRV) shows lack of flow-related signals within the left half of the distal superior sagittal sinus, left transverse sinus, and nonocclusive thrombus in the left sigmoid sinus. Mechanical sinus thrombectomy attempted without significant difference in clot burden. A transcranial Doppler (TCD) emboli monitoring exam was ordered and was performed on the bilateral internal jugular for 15 min each. Microembolic signals detected: 52 emboli per hour right internal jugular vein (IJV), and 32 emboli per hour left IJV. She was discharged on methazolamide, furosemide, topiramate, and lifelong warfarin. No major events have been reported since discharge from 2008 to 2016.